Análise de desempenho de consultas OLAP espaçotemporais em função da ordem de processamento dos predicados convencional, espacial e temporal - Joaquim Neto, Cesar (Universidade Federal de São Carlos, 2016)
By providing ever-growing processing capabilities, many database technologies have been becoming important support tools to enterprises and institutions. The need to include (and control) new data types to the existing database technologies has brought also new challenges and research areas, arising the spatial, temporal, and spatiotemporal databases. Besides that, new analytical capabilities were required facilitating the birth of the data warehouse technology and, once more, the need to include spatial or temporal data (or both) to it, thus originating the spatial, temporal, and spatio-temporal data warehouses. The queries used in each database type had also evolved, culminating in the STOLAP (Spatio Temporal OLAP) queries, which are composed of predicates dealing with conventional, spatial, and temporal data with the possibility of having their execution aided by specialized index structures. This work’s intention is to investigate how the execution of each predicate affects the performance of STOLAP queries by varying the used indexes, their execution order and the query’s selectivity. Bitmap Join Indexes will help in conventional predicate’s execution and in some portions of the temporal processing, which will also count with the use of SQL queries for some of the alternatives used in this research. The SB-index and HSB-index will aid the spatial processing while the STB-index will be used to process temporal and spatial predicates together. The expected result is an analysis of the best predicate order while running the queries also considering their selectivity. Another contribution of this work is the evolution of the HSB-index to a hierarchized version called HSTB-index, which should complement the execution options.
Keywords: Data Warehouse; Bancos de dados espaço-temporais; Data warehouses espaço-temporais; Índices bitmap; Spatio-temporal databases; Spatio-temporal Data Warehouses; Bitmap indexes; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO